Examining Factors Influencing Students’ Acceptance of Online Learning during COVID-19 Pandemic: Evidence from Thailand - Loi Chek Kim; Attapol Khamkhien; Norazah Mohd Suki; Songyut Akkakoson; Lee Hock-Ann (Malaysian Journal of Social Sciences and Humanities, 2023)
This study examines factors influencing students’ acceptance of online learning during the COVID-19 pandemic in Thailand. A self-administered questionnaire gathered from 398 students from two universities in Thailand was analysed via multiple regression analysis using the Statistical Package for Social Sciences (SPSS) version 23. This approach was utilized to evaluate eleven hypotheses. The results revealed that perceived usefulness was the predominant factor that affected students’ actual use, readiness, and motivation to use online learning. The findings indicate that when the online learning system and online content are of good quality, students will perceive online learning as valuable, which will result in more actual usage. These students would accept that it is a suitable method for completing homework, obtaining information from the Internet, and learning the English language. This study makes significant contributions to advancing the understanding of factors influencing students’ acceptance of online learning during the COVID-19 pandemic in Thailand by applying the technology acceptance model (TAM) as the guiding principle. Thailand's online learning delivery system could benefit from these empirical findings, which could be used to develop guidelines to improve its effectiveness. Directions for future research are also presented.